Incidence of Dengue Fever in Pakistan - Zarmeen Nasim; Robert C. Reiner; Sana Sheikh; Nida Saddaf Khan; Mushyada Ali; Isbaah Tejani; Mirza Tayyab Mehmood; Javerya Hassan; Khalid Aziz; Joveria Farooqi; Najia Ghanchi; Erum Khan; et al. (PLoS ONE, 2026)
Introduction Dengue is a growing health threat in Pakistan due to climate, urbanization, and inadequate sanitation. Despite recurrent seasonal outbreaks, comprehensive evidence on the dengue burden in Pakistan remains limited due to due to underreporting, incomplete data capture, and inconsistencies in diagnostic practices. Methods We analyzed laboratory-confirmed dengue cases from January 2012 to December 2022 to estimate incidence rates per 1,000 individuals across Pakistan at the subnational level including all 4 provinces, 86 districts, and a federal territory, stratified by 5 distinct age groups (below 5 years, 5–14 years, 15–49 years, 50–69 years, and 70 + years) and sex. The population estimates were adjusted to account for variations in treatment-seeking behavior and the utilization of partnering laboratories to ensure that the estimated incidence rates accurately represent the broader population. Results The incidence rate of dengue in Pakistan exhibited an increasing trend. Across all age groups, the 15–49 years age group had the highest incidence rates, with 56 cases per 1,000 individuals in 2022 (estimated 1.6 million cases). Sex analysis showed a higher proportion of dengue cases in males compared to females, consistent across all age groups. Spatial analysis revealed regional disparities, with higher incidence rates reported from Sindh compared to other provinces. In 2022, Sindh had the highest incidence rate of 45.63 (95% UI: 34.13–60.68) per 1000 individuals (2.63 million estimated cases), while Baluchistan had the lowest incidence rates of 0.44 (95% UI: 0.08–4.48) per 1,000 individuals (6,785 estimated cases). All age groups experienced increasing incidence, with the 15–49 age group showing the most pronounced rise. Conclusion The findings underscore the growing burden of dengue in Pakistan, highlighting the urgent need for effective public health interventions and enhanced data collection mechanisms to better understand and address this rising public health concern.